Empathy as a predictor of prosocial behavior and the perceived seriousness of delinquent acts : a cross-cultural comparison of Argentina and Spain - Rodríguez, Lucas Marcelo (2019)
Fil: Rodríguez, Lucas Marcelo. Pontificia Universidad Católica Argentina. Facultad Teresa de Ávila. Departamento de Humanidades. Centro de Investigación Interdisciplinar en Valores, Integración y Desarrollo Social; Argentina